Internal Academic Audit: Need Of The Hour In Hospitality Institutes, Nchmct, India ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2015)
Background : Academic audit is an important and essential part of any educational institution. It  provides the opportunity for a regular strategic overview of learning and teaching activities of any  institution in its entirety. National Council for Hotel Management & Catering Technology  (NCHMCT) is an autonomous body under Ministry of Tourism, Government of India. The council  centrally regulates academics for B.Sc. Hospitality and Hotel Administration and nine other  structured courses of study that are imparted at the existing 21 Central Institutes of Hotel  Management, 16 State Government Institutes of Hotel Management and 14 Private Institutes of  Hotel Management affiliated with NCHMCT. Methods: Data was collected by means of a  questionnaire which was sent to all the Hospitality Institutes (n=51) through e-mail under the  NCHMCT. Results: 49% institutes responded and sent back the filled questionnaire. The study  identifies that 92% IHMs recommend a well defined Internal Academic Audit is need of the hour in  Hospitality Institutes under the umbrella of NCHMCT.
Keywords: Hospitality; Academic Audit; Stakeholders; Quality Assurance